DIGITAL TRANSFORMATION OF THE LEADERSHIP AND ENTREPRENEURSHIP CONCEPTS OF TYT TUN SERI SETIA (DR) HAJI MOHD ALI BIN MOHD RUSTAM IN THE ERA AND POST PANDEMIC OF COVID-19 - Mohd Hafizuddin Mejah; Mohammad Ismail; Siti Amaliya Mohd Radyi (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Based on the technological sophistication in the field of information technology today, the digitization aspect also experiences the same increasing tendency in the need to meet the demands of general development today. According to TYT Tun Seri Setia (Dr) Haji Mohd Ali bin Mohd Rustam in terms of leadership and entrepreneurship, with the world’s population expected to reach 8.6 billion in 2030, the current development of technology predicts that 50 billion electronic devices will interact with each other. This shows that the number of devices that will communicate is greater than the number of people. Related tools from the internet and also the information that causes the emergence of the latest wave of technological sophistication that is also known as IR4 or industrial revolution 4.0 in the technology of the era of digitization transformation. Now, in human life today based on internet network connections in making a very rapid development. In a developed country that continues to record the achievement and development of proactive and trendy digitization communication for and meeting the needs of the people based on daily affairs and giving a positive effect to the science of economic development, increasing innovation and science that will also drive the economic growth of the country’s competitiveness. Therefore, this research explores the digital transformation of leadership and entrepreneurship concepts demonstrated by TYT Tun Seri Setia (Dr) Haji Mohd Ali bin Mohd Rustam during and after the Covid-19 pandemic. The study employs a qualitative approach, specifically utilizing in-depth interviews to gather comprehensive insights. The result of this study is that the transformation of digitization is a paradigm shift where it affects each other with the application of digitization and integration in all areas of human life including aspects of leadership and entrepreneurship.